A non-Arab Poet whose Song always remained Arabian. (Iqbal studies, Urdu and Lebanon) - Amir, Dr. Zahid Munir (Journal of Research in Humanities, 2023)
This article discusses the Poet-philosopher Allama Iqbal’s thought in which he claims to be an Arab poet as he says: no doubt my voice is non-Arabic, but my tone and message is purely Arabic. He declares in very clear terms __ “I have used non-Arabic languages like Persian and Urdu for disseminating my message. However, the source of my love and the basis of my tone has always been Arabic. ” This article deals with Iqbal studies and Urdu in Lebanon and provides firsthand information about the works done in Lebanon in these areas of knowledge. The author has discovered many new books and researches about Urdu language and Iqbal studies in Lebanon. Weaknesses and shortcomings of these works have also been critically evaluated in an enlightening manner.